EFFECT OF SEASON ON BIOCHEMICAL CONSTITUENTS OF SERUM IN COMMERCIAL BROILER CHICKEN (Indian Journal of Animal Production and Management, 2014)
A study was conducted on broilers in two trials to estimate blood biochemical parameters during summer and winter season. Blood samples (32 nos) were collected from two birds (one male & one female) per replicate, before slaughtering. The result revealed that the glucose concentration was significantly (p
Keywords: Biochemical constituent; season; serum; sexes